The Shah of the Safavid Hüseyin Mirza of Coins - Necla DURSUN (Fırat University, 2019)
The Safavids, one of the greatest Muslim dynasties, reigned over Iran and around. Sovereign of Hüseyin Mirza, the nineth emperor of this great dynasty, corresponds with the collapse period of the Safavids. Coins of this period generate the most challenging samples of the Safavid state in terms of coin form, style and variety of writings used. There are religious inscriptions on the front side of coins in line with Shi’a beliefs whereas name and title of the emperor and coin information are available on the back side. The language used on coins is Farsi instead of Arabic as different from other Islamic period coins. Two different font types appear on coins as a sulus and talik. While invocations and names of khalifas are taking part on front sides of coins, shah names and coin information take part on back sides. According to Shia belief, some phrases are seen such as “Ali is friend of Allah” along with “La-ilaha-illal-lah, Muham-madu’r-Rasulullah”. Sultan used the title of “shah” on almost all coins. On the coins of this period, printing date was given on the back side using numbers. Along with the esthetic outlook which talik font type gives, string of pearls on edge kerbs were used as essential pattern. Apart from geometrical forms, plantal ornamentation kerbs take part on contours of coins. There exist geometric and botanical ornament curbs on coin contours. The aim of the study is to propound scientific evaluations and comparisons of Safavids coins with other periods by examining, reading writings and assorting ornaments and compositions with art history discipline. Considering studies conducted about Safavid coins, it is seen that these are partakes of coin catalogues except for a few studies. These coins which are not considered much in terms of Islamic period coins will be introduced to science world generally.